Improvement of grinding performance and investigation of cutting parameters using a grinding mechanism with secondary rotational axis - Oktay, Adiyaman; Vedat, Savas; Sehmus, Baday (Springer London Ltd, 2018)
Grinding Mechanism having Advanced Secondary Rotational Axis (GMASRA) is one of the newer plane surface grinding methods that have an uncommon abrasion mechanism. Unlike conventional methods, in GMASRA, there are two rotations of a wheel. The first rotation is the same as in conventional grinding methods, which is the circumferential rotation. The other rotation is the newly developed axial rotation, where the wheel rotates around itself perpendicular to its radial axis. In this study, the effects of certain cutting parameters on arithmetical mean deviation of the assessed profile (the R-a parameter) were investigated. Particularly, the effects of cutting parameters on R-a in the GMASRA grinding process were examined. The selected cutting parameters were the depth of cut, the number of axial revolutions of the wheel, and the stepover distance of the wheel. Five wheels with different properties were chosen. Additionally, GMASRA was modeled using the Taguchi orthogonal test design. In this orthogonal design, the depth of cut, the spindle speed, and the type of grinding wheel were chosen as the control factors. The effect of the specified control factors on the surface roughness was demonstrated using an analysis of variance (ANOVA) test. Results show that GMASRA produced better R-a values than the conventional method. R-a values were very close to each other in every part of the ground workpieces. According to the modeling results, the spindle speed had the highest effect on R-a, followed by the depth of cut and the type of grinding wheel. GMASRA is also very cost effective and can be adapted to most milling machines and CNC milling machines.
Keywords: Grinding technique; Plane surface grinding; Surface roughness; Taguchi test design